Penerapan Group to Group Exchange (GGE) Blended Learning Berbantuan WhatsApp untuk Meningkatkan Keaktifan dan Hasil Belajar Peserta Didik SMAN 1 Jetis Ponorogo - Ulfa Ni'matil Hasanah; Susiswo Susiswo; Abd. Qohar (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2021)
The purpose of this research is to improve the condition of the online class, especially the activeness of students during the synchronous and asynchronous learning process. This study is also to determine the increase in student learning outcomes on vektor material. Learning uses the Group to Group Exchange (GGE) model in online classes and blended learning assisted by WhatsApp. This study uses a classroom action research design which consists of two cycles. The research subjects were students of Class X MIPA 1 SMAN 1 Jetis Ponorogo. Data on student activity includes discussion activities (asking or answering questions), presentations, and giving responses. This data was collected through observation sheets. Data about student learning outcomes are obtained through written tests or quizzes after the cycle takes place. Data were analyzed using descriptive statistical methods. The results of the analysis showed an increase in activity and learning outcomes after learning using the GGE steps. GGE consists of (1) material distribution; (2) group distribution; (3) group discussion in the WA group; (4) presentation and group responses in the class WA group; and (5) evaluation. Class action taken in the form of reshuffling group members and face-to-face meetings. Student activity increased, in cycle I when online using WhatsApp, all student activities were recorded on WhatsApp chat only 54%. Group discussions in the WA group were less than optimal and presentations using photo sharing and voice notes were also less than optimal. While in the second cycle when blended learning, group discussions using WhatsApp group and face-to-face while face-to-face presentations, student activity became 88%. The learning outcomes of students whose scores are greater than the KKM increased from 24% in the first cycle to 72% in the second cycle, with the class average increasing from 48.48 to 81.76. The results of this study indicate that using a GGE based on WhatsApp-assisted blended learning can significantly increase student activity and learning outcomes.